IMPLEMENTASI BENTUK KOMUNIKASI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH DASAR ISLAM TERPADU BINA INSAN BATANG KUIS - Makmur Syukri; Atika Hanan Harahap (Universitas Islam Negeri (UIN) Sumatera Utara, 2021)
ABSTRACTThis research aims to describe the Implementation of School Principal Communication Form in Improving Teacher Performance at SDIT Bina Insan Batang Kuis District. The purpose of this research is to reveal: (1) To describe the function of the Principal in communicating the vision, mission and goals of the school at SDIT Bina Insan Batang Kuis. (2) To describe the performance of teachers in SDIT Bina Insan Batang Kuis. (3) To describe the form of School Principal Communication Form in Improving Teacher Performance at SDIT Bina Insan Batang Kuis.The reasearch uses qualitative research, with a phenomenological approach, research data collection is obtained by interviewing, documenting and observing techniques. To check the validity of the data using tringulation techniques, namely with credibility, transferability, dependability and confirmability. The step of analyzing data using Milles and Hubberman's model of data analysis is to reduce data, present data and then conclude. There are three findings in this reasearch, namely: (1) The Principal's function in communicating the vision and mission and goals of the school at SDIT Bina Insan Batang Kuis using seven functions of the Principal, namely: Principal as educator, Principal as manager, Principal as administrator , Principal as supervisor, Principal as leader, Principal as innovator and Principal as motivator. (2) The performance of teachers at SDIT Bina Insan Batang Kuis has a high level of discipline, responsibility and initiative, and the teachers at SDIT Bina Insan Batang Kuis have the role of the teacher as: facilitator, administrator, demostrator, counselor, motivator, moderator and evaluator. (3) Forms of communication for school principals in improving teacher performance at SDIT Bina Insan Batang Kuis use both forms of communication, namely: verbal communication in which the principal uses polite, weak, strict and structured speech, the principal also uses non-verbal communication.